KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF PERLINDUNGAN TERHADAP KORBAN (STUDI KASUS PUTUSAN NOMOR 748/PID.SUS/2023/PN JKT.BRT) - Maulidini, Maylani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research discusses domestic violence from the perspective of victim protection. According to Law Number 23 of 2004 concerning the Elimination of Domestic Violence, it is explained that domestic violence is any act against someone, especially women, which results in physical, sexual, psychological misery or suffering, and/or domestic neglect including threats. to carry out unlawful acts, coercion or deprivation of liberty within the household sphere. Legal protection for victims of criminal acts of domestic violence is all efforts or attempts to defend and protect the rights and obligations of victims of criminal acts of domestic violence through regulations that aim to provide a sense of security to every citizen. It is hoped that Law Number 23 of 2004 concerning the Elimination of Domestic Violence will provide significant legal protection for victims of domestic violence. There are many ways to protect victims of domestic violence. Starting from temporary preventive protection from the police and courts, curative protection through repression of perpetrators, and curative protection through assistance to victims. At the West Jakarta District Court, the defendant Bambang Lasmana was found guilty of the crime of domestic physical violence against his wife, the victim witness based on decision Number 748/Pid.Sus/2023/PN Jkt.Brt. With this decision, the judge imposed a criminal sentence on the defendant.